2023
DOI: 10.1021/acssuschemeng.3c02027
|View full text |Cite
|
Sign up to set email alerts
|

Multilayer Silicene Nanosheets Derived from a Recycling Process Using End-of-Life Solar Cells Producing a Silicene/Graphite Composite for Anodes in Lithium-Ion Batteries

Yutthanakon Kanaphan,
Annop Klamchuen,
Voranan Piyavarakorn
et al.

Abstract: Silicene, with its unique two-dimensional layered Si nanosheets, has been attracting increasing attention in recent years. This is due to its graphene-like structure and outstanding anode properties. There have been a few experimental studies of anodes in lithium-ion batteries (LIBs). The main problems are limited material resources and complicated production methods, which limit their practical applications. Therefore, large-scale and high-quality fabrication of silicene using green methods and sustainable ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Yutthanakon et al reported a chemical exfoliation technique to produce 1.73–3 nm thick silicene via a relatively greener route. 63 As shown in Fig. 21, they observed a 306 mA h g −1 discharge capacity at 1C (the amount of electrical current that goes through the battery divided by the area of its layer) rate and approximately 290 mA h g −1 at 1C current density after 500 cycles with 97% retention.…”
Section: Applicationsmentioning
confidence: 89%
See 2 more Smart Citations
“…Yutthanakon et al reported a chemical exfoliation technique to produce 1.73–3 nm thick silicene via a relatively greener route. 63 As shown in Fig. 21, they observed a 306 mA h g −1 discharge capacity at 1C (the amount of electrical current that goes through the battery divided by the area of its layer) rate and approximately 290 mA h g −1 at 1C current density after 500 cycles with 97% retention.…”
Section: Applicationsmentioning
confidence: 89%
“…This result showed that silicene is semi-metallic. 63 Due to its buckling structure, the thermal conductivity of silicene is much lower than that of graphene. As a result, silicene shows great potential for application in thermoelectric devices.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation